Drug repositioning in epilepsy reveals novel antiseizure candidates. Issue 2 (11th December 2018) - Brueggeman, Leo; Sturgeon, Morgan L.; Martin, Russell M.; Grossbach, Andrew J.; Nagahama, Yasunori; Zhang, Angela; Howard, Mathew A.; Kawasaki, Hiroto; Wu, Shu; Cornell, Robert A.; Michaelson, Jacob J.; Bassuk, Alexander G.
Abstract: Objective: Epilepsy treatment falls short in ~30% of cases. A better understanding of epilepsy pathophysiology can guide rational drug development in this difficult to treat condition. We tested a low‐cost, drug‐repositioning strategy to identify candidate epilepsy drugs that are already FDA‐approved and might be immediately tested in epilepsy patients who require new therapies. Methods: Biopsies of spiking and nonspiking hippocampal brain tissue from six patients with unilateral mesial temporal lobe epilepsy were analyzed by RNA‐Seq. These profiles were correlated with transcriptomes from cell lines treated with FDA‐approved drugs, identifying compounds which were tested for therapeutic efficacy in a zebrafish seizure assay. Results: In spiking versus nonspiking biopsies, RNA‐Seq identified 689 differentially expressed genes, 148 of which were previously cited in articles mentioning seizures or epilepsy. Differentially expressed genes were highly enriched for protein–protein interactions and formed three clusters with associated GO‐terms including myelination, protein ubiquitination, and neuronal migration. Among the 184 compounds, a zebrafish seizure model tested the therapeutic efficacy of doxycycline, metformin, nifedipine, and pyrantel tartrate, with metformin, nifedipine, and pyrantel tartrate all showing efficacy. Interpretation: This proof‐of‐principle analysis suggests our powerful, rapid, cost‐effective approach can likely be applied to other hard‐to‐treat diseases.